Expression of existential suffering in two patients with advanced cancer in an acute palliative care unit. Issue 6 (December 2020) - Tang, Michael; Nguyen, Nhu-Nhu; Bruera, Eduardo; Tanco, Kimberson; Delgado-Guay, Marvin
Abstract: Background: Recognizing and managing existential suffering remains challenging. We present two cases demonstrating how existential suffering manifests in patients and how to manage it to alleviate suffering. Case description: Case 1: A 69-year-old man with renal cell carcinoma receiving end-of-life care expressed fear of lying down "as he may not wake up." He also expressed concerns of not being a good Christian. Supportive psychotherapy and chaplain support were provided, with anxiolytic medications as needed. He was able to express his fear of dying and concern about his family, and Edmonton Symptom Assessment System scores improved. He died peacefully with family at bedside. Case 2: A 71-year-old woman presented with follicular lymphoma and colonic obstruction requiring nasogastric drain of fecaloid matter. Initially, she felt that focusing on comfort rather than cure symbolized giving up but eventually felt at peace. Physical symptoms were well-controlled but emotionally she became more distressed, repeatedly asking angrily, "Why is it taking so long to die?." She was supported by her family through Bible readings and prayers, but she was distressed about being a burden to them. An interdisciplinary approach involving expressive supportive counseling, spiritual care, and integrative medicine resulted in limited distress relief. Owing to increasing agitation, the patient and family agreed to titrate chlorpromazine to sedation. Her family was appreciative that she was restful until her death. Conclusion: Existential suffering manifests through multiple domains in each patient. A combination of pharmacologic and non-pharmacologic techniques may be needed to relieve end-of-life suffering.